FUNCTIONALITY OF THE KSU FEEDBACK 3.0 - Spivakovsky, A.; Berezovsky, D.; Tityenok, S. (Journal of Information Technologies in Education (ITE), 2012)
Evolution of e-service “KSU Feedback”, analyzing the flaws and limitations of the old version of “KSU Feedback 2.0 RC1”, review of functionality and a key features of the upcoming release “KSU Feedback 3.0”.